Investigation on the breeding cycle of palm cockatoos (Probosciger aterrimus) in captivity : perspective from the egg. - Chua, Xiu Xia. (2011)
Very few field studies are done on the breeding activity of wild Probosciger aterrimus (Palm Cockatoo) while they are inside their nests due to the challenges of locating nesting hollows and making field observations without disturbing the birds. In this study, 24-hour camera surveillance was carried out to observe the breeding activity of two pairs of captive Palm Cockatoos, through the perspective of the egg’s life cycle. The focus of this project was to study egg attentiveness which was defined as the percentage of time the egg was accompanied by at least one parent inside the nest, as well as, the types of attention given to the egg from the parents. Results showed that only the female Palm Cockatoo incubated the egg at night while the male Palm Cockatoo was more involved in egg turning during the day. The differences in the types of attention given by the male and female may imply specific parental roles. Nocturnal egg neglect was observed on three nights but did not affect the egg’s viability may imply that continuous incubation was unnecessary. Further investigation could be made with larger sample size to confirm these results.